Evaluation of the potential of 99mTc-PEI-MP for diagnosis and follow-up, in a comparative study using in vivo models of bladder cancer and osteosarcoma - Ferreira, Sara (2014)
Introduction: The aim of this study was to evaluate in vivo the efficacy of 99mTc-PEI- MP (polyethyleneiminomethyl phosphonic acid) for diagnosis of bladder cancer and osteosarcoma